Proposta de atividades com metodologias ativas no ensino de ondulatória com enfoque na música - VIEIRA, Antônio Lindomar Silva (2023)
This work discusses the importance of using pedagogical methodologies to enable quality teaching and learning of physics for basic education students. In particular, the active methodology will be addressed in line with the fundamentals of Wavemaking, focusing on acoustics, sound waves and music. This study analyzes the benefits and challenges faced by teachers and students when using this teaching resource, based on a complementary review of the literature from the perspective of Vygotsky and Piaget. Furthermore, the following are presented: (1) practical examples and concepts relevant to music; (2) how the study of music can contribute to the development of learning in physics in elementary and high school despite involving complex terms. Based on this, it is clear that teaching and learning end up becoming a mutual process, between the content presented by the teacher and the practice based on the experiments that students present on the subjects of exact sciences. Next, the previously mentioned contents are exemplified in greater depth, through an application proposal using the following strategies: problem-based learning; project-based learning; invested classroom and inquiry-based learning. Finally, these strategies are modeled in the context for teaching Wave Physics (sound waves, frequencies, soundtracks and others).